Calculation of anharmonic effect on the reactions of small sulfur‐containing molecules with NO/NO2 in combustion. Issue 10 (11th July 2021) - Hu, Wenye; Chen, Yuanpeng; Yang, Kun; Yu, Hongjing; Wang, Shiye; Yao, Li
Abstract: Nitrogen oxides and sulfur oxides are the main pollutants that destroy the atmosphere, the emission and control of which have received wide attention. Notably, the interactions between nitrogen species and sulfur species occur extensively in combustion and the atmosphere. This article summarizes the 12 reactions of small sulfur‐containing molecules with NO/NO2 in combustion. The reaction rate constants of the 12 reactions at the temperature ranging from 300 to 4, 000 K are calculated according to YL (Yao‐Lin) method and TS (transition state) theory. The results show that there is a large difference between the anharmonic and the harmonic rate constants for many reactions, especially at high temperature. In particular, the calculated values of the reactions S + NO2 → SO + NO, N + SO2 → SO + NO, and SH + NO2 → HSO + NO are in good agreement with other theoretical or experimental ones. Finally, the kinetic and thermodynamic parameters are calculated according to the anharmonic and harmonic rate constants as well as the least square methods. All these indicate that the anharmonic effect cannot be ignored and YL method is feasible. Abstract : 1. As temperature increases, the harmonic and anharmonic rate constants increase and anharmonic effect also increases. 2. There is a junction of the rate constants within the scope of the low temperature ranging from 400 to 1, 400K. 3.The calculated values in this work are in good agreement with the reference values, which proves the feasibility and reliability of the YL method to calculate the harmonic and anharmonic rate constants.